Desubalternity: A Psychoanalytical Study of Displacement of Emotions in Carol Ann Duffy’s The World’s Wife - Mashal; Siddiqui, Bushra (Pakistan Languages and Humanities Review, 2024)
The research examines the characters and their interrelated relationships as an outlet of their psychological burden which they share as same sex. By scrutinizing the elements of psychological displacement of emotions, the research tries to identify the gap between the realities and how by giving voice to these characters, the repressed desires are being transferred and changing the narrative for the reader. The research analyzes selected poems from the collection The World’s Wife by Carol Ann Duffy through the lens of psychoanalytical process of displacement. The selected poems deconstruct the gender politics and emphasize on the narrative of the silenced female mythological and historical figures. By identifying displacement of emotions in the female characters and analyzing those emotions through introversion and the gender politics that it creates, the concept of desubalternity comes to shore. The research actively traces the collective metamorphosis of the female characters without being a critique on masculinity which paints the complex image of the phenomenon of being doubly marginalized and how these characters’ model introversion through desubalternity. The paper suggests that peeling both layers of marginalization is required to gain a true sense of power.